Planning and development of agricultural production in the Shamiya district (Journal of the College of Basic Education, 2022)
The research paper focused in its study on the planning and development of agricultural production (plant) represented by agricultural crops within the geographical area represented by Al-Shamiya district, with its administrative borders, which represents one of the districts of Al-Qadisiyah Governorate. 1 3° and (46-31°) in the north, longitudes (31 44°) and (43 44°) in the east, and it is bounded by the north in the direction of Salihah, in the east by al-Shafi’iyyah, in the south by Ghammas, and in the west by the Najaf governorate. The research was concerned with studying planning for the use of modern technologies in agricultural production of both types (plant and animal), as well as planning for intellectual development, raising awareness and education in the field of agricultural sciences, seeds and fertilizers, and providing technical information for farmers. Increasing farmer productivity and balanced agricultural investments that ultimately lead to the foundations upon which planning for sustainable agricultural development rests.